Transfusion reaction - Signs and symptoms and hemovigilance interventions (International Seven Journal of Multidisciplinary, 2024)
The aim of this study was to review the literature on transfusion reactions - signs and symptoms and hemovigilance interventions. This is a bibliographical review of the literature. Scientific materials were used from the databases - Latin American and Caribbean Literature in Health Sciences - Lilacs, and Scientific Electronic Library Online - Scielo, and articles related to "Blood component transfusion" were selected. Despite the regulations and the efforts of the National Health Surveillance Agency (ANVISA), together with the sentinel networks, there is still under-reporting of transfusion reactions in Brazil. This makes it more difficult to control and recognize occurrences. Transfusion reactions cause varying degrees of damage to the patient and can be immediate: when signs and symptoms appear during the blood transfusion or up to 24 hours after the start of infusion therapy. As an integral part of the health system, all health professionals must achieve an optimum standard of patient care, prioritizing quality care and good practices in the management of patients who need to be transfused.